2012
DOI: 10.1002/eji.201141982
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced FRI‐mediated neutrophil migration towards tumour colonies in the presence of endothelial cells

Abstract: Neutrophils potently kill tumour cells in the presence of anti-tumour antibodies in vitro.However, for in vivo targeting, the neutrophils need to extravasate from the circulation by passing through endothelial barriers. To study neutrophil migration in the presence of endothelial cells in vitro, we established a three-dimensional collagen culture in which SK-BR-3 tumour colonies were grown in the presence or absence of an endothelial barrier. We demonstrated that -in contrast to targeting FcγR on neutrophils w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 32 publications
0
26
0
2
Order By: Relevance
“…This induces a positive migration loop that can be very efficient for killing invading bacteria at mucosal sites where IgA is the predominant Ab (14). Moreover, we also showed that targeting FcaRI very effectively induced leukotriene B4-dependent neutrophil recruitment into tumor colonies, which led to destruction (38). Thus, we postulated that FcaRI may promote tissue damage in diseases mediated by IgA autoantibodies.…”
Section: Discussionmentioning
confidence: 66%
“…This induces a positive migration loop that can be very efficient for killing invading bacteria at mucosal sites where IgA is the predominant Ab (14). Moreover, we also showed that targeting FcaRI very effectively induced leukotriene B4-dependent neutrophil recruitment into tumor colonies, which led to destruction (38). Thus, we postulated that FcaRI may promote tissue damage in diseases mediated by IgA autoantibodies.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, targeting FcαRI, but not FcγR, resulted in neutrophil migration. Destruction of either mamma carcinoma or colon carcinoma colonies in three‐dimensional culture systems was observed due to LTB4 release and concomitant neutrophil accumulation after cross‐linking of FcαRI . It was furthermore demonstrated that targeting FcαRI on neutrophils induces autophagic tumor cell death and to a lesser extent tumor necrosis .…”
Section: Fcαri In Anti‐tumor Immunotherapymentioning
confidence: 99%
“…6,7 Moreover, IgAmediated FcaRI activation appears to actively recruit PMN toward tumor cells. 8,9 Since tumor-killing by IgA depends on activation of the FcaRI and that of IgG1 is assumed to be mainly mediated by FcgRIIIa, it might be superior to the corresponding IgG1 when treating patients carrying the FcgRIIIa F158 allele in whom IgG1 efficacy is reduced compared to carriers of the V158 allele. 10,11,12 Very recently, it has been demonstrated not only that macrophages can mediate tumor cell killing by IgA2, but more importantly that this occurs in vivo.…”
Section: Introductionmentioning
confidence: 99%